Reduced Intrinsic Non-Radiative Losses Allow Room-Temperature Triplet Emission from Purely Organic Emitters - Li, Yungui; Jiang, Lihui; Liu, Wenlan; Xu, Shunqi; Li, Tian-Yi; Fries, Felix; Zeika, Olaf; Zou, Yingping; Ramanan, Charusheela; Lenk, Simone; Scholz, Reinhard; Andrienko, Denis; et al. (Advanced Materials, 2021)
Persistent luminescence from triplet excitons in organic molecules is rare, as fast non-radiative deactivation typically dominates over radiative transitions. This work demonstrates that the substitution of a hydrogen atom in a derivative of phenanthroimidazole with an N-phenyl ring can substantially stabilize the excited state. This stabilization converts an organic material without phosphorescence emission into a molecular system exhibiting efficient and ultralong afterglow phosphorescence at room temperature. Results from systematic photophysical investigations, kinetic modeling, excited-state dynamic modeling, and single-crystal structure analysis identify that the long-lived triplets originate from a reduction of intrinsic non-radiative molecular relaxations. Further modification of the N-phenyl ring with halogen atoms affects the afterglow lifetime and quantum yield. As a proof-of-concept, an anticounterfeiting device is demonstrated with a time-dependent Morse code feature for data encryption based on these emitters. A fundamental design principle is outlined to achieve long-lived and emissive triplet states by suppressing intrinsic non-radiative relaxations in the form of molecular vibrations or rotations.
CRIS-Team Scopus Importer:2023-03-20
Keywords: non-radiative loss; phenanthroimidazole; room-temperature phosphorescence; triplet emission